Numerical Investigation On The Polymer Flow In A Restriction Flow Path - Fishal, Nur Fitrah (Universiti Sains Malaysia, 2022)
Rheology is the studies of deformation and flow of material when force is applied on it. Rheology studies is crucial for the processing technique and the successful of it is depends on the controlling rheological behavior of the polymer melts. The shear flow behavior can be controlled by adjusting the processing variable such as temperature, shear, pressure and many more. This study aims to simulate the flow of ABS inside the capillary rheometer and melt flow indexer (MFI), and also to determine the effect of temperature on the rheology properties of the polymer. The 2D model of capillary rheometer and 3D model of melt flow indexer (MFI) were designed to simulate the flow of ABS using Ansys Fluent. Comparative evaluation between experiment and simulation were done at different temperature. For the capillary rheometer, temperature used were 200℃ and 220℃, while for MFI, the temperature used were 250℃, 260℃, 270℃. The result demonstrate the experiment and simulation develop almost the same pattern. The curve of viscosity against shear rate depicts almost similar result. As shear rates increases, the viscosity reduced. Also as temperature was increases, the viscosity of polymer melt reduced due to disentanglement of molecular chain. Generally, the temperature influences the flow properties of the ABS polymer melt.